Poetry and Vision in Early Modern England - Partner, Jane (Early Modern Literature in History, 2018)
This book reveals the ways in which seventeenth-century poets used models of vision taken from philosophy, theology, scientific optics, political polemic and the visual arts to scrutinize the nature of individual perceptions and to examine poetry's own relation to truth. Drawing on archival research, Poetry and Vision in Early Modern England brings together an innovative selection of texts and images to construct a new interdisciplinary context for interpreting the poetry of Cavendish, Traherne, Marvell and Milton. Each chapter presents a reappraisal of vision in the work of one of these authors, and these case studies also combine to offer a broader consideration of the ways that conceptions of seeing were used in poetry to explore the relations between the 'inward' life of the viewer and the 'outward' reality that lies beyond; terms that are shown to have been closely linked, through ideas about sight, with the emergence of the fundamental modern categories of the 'subjective' and 'objective'. This book will be of interest to literary scholars, art historians and historians of science.